Psychological Capital Mediates the Association Between Perceived Organizational Support and Work Engagement Among Chinese Doctors - Shihan Yang; Hao Huang; Tian Qiu; Fangqiong Tian; Zhihui Gu; Xuege Gao; Hui Wu (Frontiers Media S.A., 2020)
Background: As experts studying occupational health psychology know, low level of work engagement leads to higher turnover intentions. Some researchers have put a focus on the association between organizational support and work engagement. However, little has been done concerning the mediating effect of psychological capital (PsyCap) on the association between perceived organizational support (POS) and work engagement (vigor, dedication, absorption) among Chinese doctors.Methods: A cross-sectional study has been carried out from November to December in 2017, in Liaoning Province, China. The questionnaire consists of Survey of Perceived Organizational Support, the Utrecht Work Engagement Scale, Psychological Capital Questionnaire, and demographic and working variables. The self-administered questionnaires were distributed to 1,009 doctors. Effective responses were collected from 836 participants (82.85%). Hierarchical multiple regression and the asymptotic and resampling strategies were used to examine the association between POS and work engagement mediated by PsyCap.Results: After controlling the demographic and working variables, POS was positively related to vigor (β = 0.402, P < 0.01), dedication (β = 0.413, P < 0.01), and absorption (β = 0.373, P < 0.01). Psychological capital was positively associated with vigor (β = 0.442, P < 0.001), dedication (β = 0.413, P < 0.001), and absorption (β = 0.395, P < 0.001). Thus, PsyCap [a × b = 0.1895, bias-corrected and accelerated 95% confidence interval (BCa 95% CI) = 0.1524, 0.2290]; a × b = 0.1517, BCa 95% CI = 0.1180, 0.1875; a × b = 0.1693, BCa 95% CI = 0.1299, 0.2099] significantly mediated the association between POS and vigor, dedication, and absorption, respectively.Conclusion: There was a low level of work engagement among Chinese doctors. Perceived organizational support could indirectly improve vigor, dedication, and absorption, partially through mediator PsyCap. Perceived organizational support intervention, education, and training in PsyCap should be carried out to cope with work engagement.